CONNOTATIVE CHARACTER OF NAMES OF WILD BIRDS IN RUSSIAN AND UZBEK LANGUAGES (Scientific journal of the Fergana State University, 2023)
The article is devoted to the study of the semantic structure of the ornithological vocabulary of the Russian and Uzbek languages. It reveals the connotative meanings of the names of wild birds in the composition of stable combinations of words in different system languages, gives examples of their functioning in the texts of fiction, and also reveals the correspondence of clichéd units with the keyword-ornithonym in these two languages.